CIPP Evaluation Modeling on BBQ Program at Baitul Quran Daarut Tauhiid Institute - Novansyah, Imbar; Saepudin, Asep (Universitas Pendidikan Indonesia (UPI), 2023)
Looking back as a whole a system that has been running normally requires an in-depth activity effort about it, one of which is by evaluating each evaluation carried out on a program, as if the program will have a new perspective of information. The purpose of this research is to get an overview of the model of a program. This research was conducted using a case study at the baitul quran institution in the BBQ program against one manager, two teachers and one program participant. Data were collected through interviews, observations and document studies. The data analysis used was qualitative content analysis using Atlas.Ti software. The results found that the CIPP evaluation model will produce a modeling of each aspect. Context there are expectations, reality and solutions. Inputs are funds, management, program strategies, resources and infrastructure. Process there are learning patterns, teacher understanding, habituation, advanced services, customized, easy access, teaching material modules. Product is program evaluation, learning evaluation, program focus, award, program test.